Synergy of Traditional Ecological Knowledge (TEK) and Intellectual Property Rights (IPR) in Biodiversity Management and Conservation - Chakraborty, Sagnik (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Indigenous and local communities’ Traditional Ecological Knowledge (TEK) is a priceless source of information about animal behaviour, habitat, and traditional uses of wildlife. As the knowledge has grown and passed from one generation to another, it has played a pivotal role in biodiversity conservation. Nevertheless, blending TEK with zoology studies in intellectual property rights (IPR) poses separate challenges as well as benefits. The article explores the intricate relationship between TEK and IPR by emphasizing the significance of preserving this knowledge for its continuous contribution to biodiversity conservation and sustainable development. The research seeks to provide an extensive analysis of different legal frameworks such as international agreements and national laws that protect TEK. It further underscores the implementation of sui generis systems that are tailored specifically for traditional knowledge which cannot be categorized under any conventional IPR. This paper also provides practical examples of how TEK can be interwoven with other forms of knowledge to enhance scientific research and conservation. Illustrations are provided here about why benefit-sharing arrangements must recognize Indigenous people and local communities’ contributions. Among other important aspects, such agreements should lead to financial compensations, support capacity development efforts, provide co-authorship opportunities as well as promote technology transfer thus effectively empowering these communities. Besides; the research under discussion highlights several ethical issues that come into play while using TEK including showing respect for cultural values and customary laws held by those who own such knowledge. It therefore calls for an inclusive approach that encourages the development of trust and mutual respect among scholars and indigenous peoples. To this end, the article offers comprehensive techniques that will help improve the safeguarding of traditional ecological knowledge (TEK), to establish legally robust yet ethically considerate policies that preserve its relevance in zoological research and biodiversity conservation today.